Experimental observation of the maximum bubble diameter in non-stationary temperature field of subcooled boiling water flow. (September 2018) - Levin, A.A.; Khan, P.V.
Highlights: The unsteady nucleate boiling of subcooled water was investigated. The data of 34 experiments was processed, 3034 maximum diameters were detected. We found that the increased heat flux results in reduction of the maximum diameter. The experimental data was compared with the Prodanovic and Song correlations. We conclude that the analytical approaches cannot be used for the unsteady nucleation. Abstract: This paper presents results of the experimental study of the subcooled boiling flow on the surface of the vertical cylindrical steel heater. The initial stages of formation of the fully developed nucleate boiling were investigated over the unsteady stepwise heat flux range from 0.56 to 1.76 MW/m 2 . The field temperature of heated liquid layers at the moment of the bubble departure was described by numerical modeling under nonstationary conditions. A high-speed digital video camera was used to capture the bubble dynamics. The effects of heat release conditions and inlet water temperature on the bubble maximum diameter and nucleation frequency were studied. We found that the increased heat flux results in reduction of the maximum diameter at non-stationary heat release. Calculations on the basis of prediction models showed that the non-stationary nucleate boiling data cannot be generalized using the models developed by Prodanovic et al. (2002) and Song (2016) with the coefficients obtained for the stationary boiling. However, the heat balance approach to calculation of the bubble maximum diameter proved to be promising, and the correlation between the bubble diameter and the overheated layer thickness was verified.